The visual fields of Common Guillemots Uria aalge and Atlantic Puffins Fratercula arctica: foraging, vigilance and collision vulnerability. (7th August 2015) - Martin, Graham R.; Wanless, Sarah; Wanless, Ross
<x xml:space="preserve">Abstract</x> Significant differences in avian visual fields are found between closely related species that differ in their foraging technique. We report marked differences in the visual fields of two auk species. In air, Common Guillemots Uria aalge have relatively narrow binocular fields typical of those found in non‐passerine predatory birds. Atlantic Puffins Fratercula arctica have much broader binocular fields similar to those that have hitherto been recorded in passerines and in a penguin. In water, visual fields narrow considerably and binocularity in the direction of the bill is probably abolished in both auk species. Although perceptual challenges associated with foraging are similar in both species during the breeding season, when they are piscivorous, Puffins (but not Guillemots) face more exacting perceptual challenges when foraging at other times, when they take a high proportion of small invertebrate prey. Capturing this prey probably requires more accurate, visually guided bill placement and we argue that this is met by the Puffin's broader binocular field, which is retained upon immersion; its upward orientation may enable prey to be seen in silhouette. These visual field configurations have potentially important consequences that render these birds vulnerable to collision with human artefacts underwater, but not in air. They also have consequences for vigilance behaviour.